Peningkatan Lipid dunaliella salina dengan Variasi Konsentrasi N2 - Elida Purba; Wildan Arief Rohdina (Balitbangda Provinsi Lampung, 2017)
This study discussed the effect of N2 concentration variation on the acquisition of amount of Dunaliella salina lipid with light intensity of 3000 lux. This study aimed to determine the appropriate concentration of N2 to obtain Dunaliella salina lipid at maximum. Photosynthesis took place in a photobioreactor with a volume of bioreactor 2 l (500 ml Dunaliella salina, 1500 ml sea-water, with variations of N2 0.06, 0.07, 0.08, 0.09 and 0.1 M) with a total gas flow rate of 5 l/min. Culture was done for 5 days and harvested biomass on the 5th day. The results showed that there was an increase in lipid yield as the N2 concentration was increased. The maximum amount of lipids obtained in the variation of N2 0.1 M was 2.3727 %